Structural and Optical Properties of ZnS Thin Films Prepared by Spray Pyrolysis Technique - Saeed, Nada M (Al-Nahrain Journal of Science, 2011)
Zinc Sulfide (ZnS) is important II-VI semiconductors material for the development of various modern technologies and photovoltaic applications. ZnS thin film was prepared by using chemical spray pyrolysis technique. The spray solutions contains ZnCl2 and SC(NH2)2 with molar concentration 0.1M/L. ZnS thin films was growth onto hot glass substrates at substrates temperature 400оC. The Structure of the prepared film was studied from X-ray diffraction pattern, the results shows that the film was polycrystalline with hexagonal structure, the grain size of ZnS film was calculated, it was 139 Å at the high peak. The optical properties of the film were studied using measurement from UV–VIS spectrophotometer; the results appear that a good optical transparency of about 65 % was observed in the visible region. The optical constants were studied as a function of the photon energy within the wavelength in the range (300-900) nm. The refractive index was calculated in the visible region, it was 2.45 at 500 nm. The optical band gaps for the direct and indirect transition were estimate too and it was 3.2 – 3.1 eV respectively.